KARAKTERISTIK TEKTONIK DAN PERIODE ULANG GEMPA BUMI PADA SESAR MATANO SULAWESI SELATAN - Hariani, Hariani; Said L, Muh.; Wahyuni, Ayusari (Universitas Islam Negeri Alauddin Makassar, 2018)
This research aims to determine the tectonic characteristics of the Matano Fault by looking at the a-value and b-value values and the period of earthquake occurrence. Matano fault is an active fault in Sulawesi. So the potential for earthquakes in this area is quite high. By analyzing the earthquake return period, especially for earthquakes with large magnitudes, we can estimate when approximately large earthquakes will occur again and anticipate in dealing with them. Based on the results of research using the Least Square method and the Likelihood the value of a-value (earthquake activity) is higher than the b-value (local rock conditions). This indicates that seismic activity in Matano fault is relatively high. Whereas for b-value (rock condition) The greater the b-value the greater the level of rock fragility and vice versa. In determining the level of seismicity in an area using two methods, namely the least square method with a b-value of 0.310 and a-value of 3.177 while for the Likelihood method a b-value of 0.315 and an a-value of 2,551 from the two methods obtained by different regions that matano faults which have high seismicity or earthquake prone areas. From the calculation using the Least Square method, the fastest return period for M tercepat 4 is around 4 years and the longest is around 23 years while the results obtained from the Likelihood method are the fastest return period around 5 years and the longest is around 48 years.